The United Kingdom’s Grocery E-Commerce Supply Chain: A qualitative analysis and comparison with Vietnamese Market - Nguyen, Anh Thu (2016)
Since the price war in 2014, the United Kingdom’s (UK) grocers have been fiercely competing for market share, yet the German discounters seem to be temporary winners. The data demonstrated a downturn in market shares of some biggest national retailers like Tesco, Sainsbury’s and Asda despite their continuous efforts on improving both services and products quality in their supermarkets network. Therefore, developing grocery E-commerce in the context of a multi-channel system seems to be a better direction than ever for those giants, given its tough facilities and infrastructure requirements. Almost every supermarket in the UK has tried to go online, though they seems to be struggling with making profit from it, as based on some recent reports, supermarkets are losing £300m per annum for operating online grocery. Consequently, this research is conducted to help the UK retailers and researchers understand more about the online grocery’s nature including its components, potentialities and characteristics, which they can base on to generate appropriate development strategies on this segment. Essentially the overall target is helping grocers to improve their E-Commerce performance, but specifically this study is conducted for three ultimate purposes: (i) investigating the characteristics of UK’s Grocery E-Commerce supply chain; (ii) comparing the environments of two markets developing at different levels: the UK-as a robust market, and Vietnam-as an emerging market; and (iii) assessing the influence of those differences on good practice of each economy and suggesting how those companies can make use of their business environments to strengthen their operations. Several well-known business analysis models are applied in the study to make sure that it delivers a credible and meaningful analysis. The study also gives numerous practical recommendations for firms to overcome their supply chain risks and exploit their surroundings.